Developments in CD4 and Viral Load Monitoring in Resource-Limited Settings. (11th November 2013) - Rowley, Christopher F.
Abstract : New technologies that provide low-cost, point-of-care testing for CD4 count and human immunodeficiency virus (HIV) load have the potential to improve care by shortening the time between diagnosis and staging and allowing real-time monitoring of the treatment of HIV-infected individuals. Abstract: CD4 counts and human immunodeficiency virus (HIV) load testing are essential components of HIV care, and making these tests available in resource-limited settings is critical to the roll-out of HIV treatment globally. Until recently, the evidence supporting the importance of laboratory monitoring in resource-limited settings was lacking, but there is now a consensus emerging that testing should become routine to ensure the longevity of treatment programs. Low-cost, point-of-care testing offers the potential to fill this role as it potentially improves all aspects of HIV care, ranging from the diagnosis and staging of HIV infection in both infants and adults to monitoring for treatment failure once antiretroviral therapy has been initiated. It is imperative for low-cost solutions to become a reality, but it is equally imperative that close scrutiny be given to each new device that hits the market to ensure they perform optimally in all settings.